Physical Therapy Training Assistance for Inclusion Groups of Persons with Disabilities in Ngawonggo Village, Malang Regency - Marsudi Dedi Putra; Mukhammad Soleh; Himawan Estu Bagijo; Regithai Putri Erlanha; Siti Naharotun Nikmah (Universitas PGRI Semarang, 2025)
Inclusive design provides space for minorities, namely people with disabilities, to have equal rights and obligations, equal dignity and status, and have the same role and position in the life of the village community. The Ngawonggo Village Government, Malang Regency, has sought legal protection for people with disabilities by establishing Village Regulation Number 2 of 2023 concerning the Establishment of Village Disability Inclusion Groups. However, based on the situational analysis, there are still problems in the implementation of Village Regulation Number 2 of 2023 concerning the Establishment of Village Disability Inclusion Groups, especially the non-optimal implementation of the duties and functions of the inclusion group concerning physical therapy training. As a result, it slows down the achievement of independence for people with disabilities and their families. Therefore, the purpose of this community service is to optimize the realization of the duties and functions of the inclusion group as an effort to accelerate independence for people with disabilities through physical therapy training.